Maximizing Profit In Broiler Chicken Farming Through Linear Programming - Natalia Vania Tjandra; Boston Sitinjak; Michael Kris Tefen; Mikhael Kevin; Wilson Vernandy; Dudy Efendy (Pinisi Journal of Social Science, 2024)
One of the broiler farming businesses that still has problems optimizing profits is the broiler farming business owned by Mr Jonathan Verian Remba. Mr Jonathan's broiler farming business operates with 3 employees. So Mr Jonathan has not been able to optimize profits and management in his business management. Therefore, the aim of this research is to find out how much profit optimization is obtained. The method used is linear programming with the simplex method, where this method is a method that utilizes information technology, namely the use of POM-QM tools to calculate maximum profit.